Investment Policy Review - Ethiopia - Conference des Nations Unies sur le commerce et le développement (United Nations, 2002)
With the signing of the peace agreement between Ethiopia and Eritrea in December 2000, effectively ending the two-year conflict between the neighboring countries, there is a renewed hope that Ethiopia will regain the economic growth momentum that it experienced in the post 1992 liberalization period. Key ingredients for renewed growth are increased investment, both domestic and foreign, in supply capacity, including physical infrastructure, the generation of relevant skills and the development of competitive enterprises through local technological and innovative capability building.